Trihybrid nanofluid flow through nozzle of a rocket engine: Numerical solution and irreversibility analysis - Basharat Ullah; Rabia Rehman; Hafiz Abdul Wahab; Umar Khan; Walid Emam (Energy Exploration & Exploitation)
Research Problem: The research investigates the process of heat transmission and the production of entropy within the regenerative cooling channel of a rocket engine. The primary focus of the investigation is on the use of nanoparticles (titanium dioxide, copper oxide, and alumina dioxide) that are dispersed in water as the base fluid. Within the context of the cooling system, the research endeavors to gain an understanding of the influence that these nanofluids have on hydrothermal performance and entropy production. Methodology: The investigation transforms similarity to reduce the governing equations to a non-dimensional form. We solve the altered equations using a shooting technique and the reduced Kutta-4 (RK-4) numerical method. With a particular focus on the Nusselt number and entropy generation number, graphic representations highlight the important parameters affecting hydrothermal performance. Implications: The results emphasize how well water-based nanofluids work, especially titanium dioxide (TiO 2 ), as a coolant in rocket engines. The work also clarifies how different parameters affect the entropy creation in the system. The importance of this study is in its possible use to improve the design of regenerative cooling systems in aeronautical engineering, therefore raising overall performance and efficiency. Future work: More investigation into the manipulation of fluid characteristics and nanoparticle concentrations should improve rocket engine cooling efficiency even more. Alternative nanoparticle materials and their impact on entropy generation and heat transport might also be investigated. Moreover, experimental validation of the numerical results can offer important information for the practical use and validation of the suggested approaches.